The Saudi-Islamic alliance project and the position of the Zionist entity (Analytical study of American documents) - Saad Mahdi Jaafar ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The study addresses the basic objectives behind King Faisal of the Kingdom of Saudi Arabia proposing the Islamic alliance project as an alternative to the Arab nationalist movement, as part of the competition between Saudi Arabia and Egypt for leadership, especially after the increase in the national stature of President Gamal Abdel Nasser. Its most important comes from its reliance on Arab books and documents on the one hand, and its main reliance on American documents that revealed the facts of cooperation between the Islamic alliance countries, especially Saudi Arabia, with the Zionist entity to negate the plans against the Arab nation, especially Egypt, which were implemented practically to exhaust Egypt for more than five years (1962-1967). It succeeded in occupying the Egyptian forces in the civil war.